Impact of plant diversity in potato-ley strip-cropping systems on soil microbial communities - Riggi, L.G.A.; Ranheim Sveen, T.; Castaño, Carles; Onorati, P.; van Apeldoorn, D.F.; Berri, M.; Mommer, L.; Clemmensen, K.E.; Bahram, M. (Elsevier, 2025)
Crop diversification enhances agroecosystem productivity, yet underlying mechanisms, particularly those underground, remain unclear. Diversification practices, such as strip-cropping (alternating strips of different crops) and integrating legumes (plant-based fertilization), may improve nutrient uptake and reduce pathogen build-up via soil microbial community shifts. However, most evidence for plant diversity benefits arises from grasslands, and its impact in cropping systems remains underexplored. This study examined microbial communities in organically managed, long-term potato-ley strip-cropping systems, comparing mono-cropping and strip-cropping, and further examined the effect of replacing animal manure by integrating legumes and plant-based fertilization in strip-cropping systems. To assess changes in microbial community composition, bacterial, fungal and arbuscular mycorrhizal fungi (AMF) DNA was sequenced. In addition, AMF and potato fungal pathogens were quantified using quantitative PCR. Strip-cropping increased AMF and soil-borne potato pathogens at the strip edges, where ley and potato interacted, though edge effects were absent in plant-based strip-cropping systems. Despite higher pathogen abundance at the edges, these did not relate to more significant tuber disease symptoms or yield losses. Changes in soil abiotic properties, particularly lower pH, from plant-based management, influenced fungal community structure more than strip-cropping. Bacterial community structure, including N-fixing bacteria, remained unaffected by either practice. Our results indicate that legume legacy in plant-based systems more strongly affected fungal community than strip-cropping, while strip-cropping benefitted AMF abundances. Taken together, our findings suggest that for sustainable agricultural practices aiming to improve soil health and crop productivity, a comprehensive approach that considers crop diversity, soil management, and fertilization practices is necessary.
Keywords: arbuscular mycorrhizal fungi; crop diversity; mixed-legume mulching; microbial community; Solanum tuberosum; strip-cropping